(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2010)
The interdisciplinary study of two deep cores drilled in Pleistocene basin fill at Northern margin of Po Plain, has been integrated with qualitative and quantitative malacological analysis. The potential of quantitative malacological analysis, to refine results obtained from interdisciplinary studies, is here highlighted. The evolution of malacological assemblages has been recorded and correlated to the general regressive trend recognized all over the Po Basin. Lower Pleistocene marine deposits, found at core base (Jaramillo Subchron and older), were gradually replaced by transitional and continental deposits since latest early Pleistocene. Area was eventually covered by continental conglomerate deposits (“Ceppo” facies) during middle-late Pleistocene. Within this general trend, regional significance of a major unconformity (“r” surface), related to onset of Pleistocene glacial cycle, is confirmed. However, as evidenced by malacology, the roughly synchronous onset of coarse clastic progradation did not result in a synchronous shift from marine to transitional and continental settings all over the study area, as an effect of inherited topography and other local factors. During marine sedimentation, fossil record allowed us to recognize a transgressive event, reliably correlated to Marine Isotope Stage 35.